A GROUNDBREAKING INFRASTRUCTURE FOR COTTON-TEXTILE CLUSTERS THAT INTRODUCES NEW AND CREATIVE ELEMENTS: 1-SON 3-TO’PLAM IYUL 2023 yil - Student of Tashkent State university of Economics, Izzatulloev Bakhodir Ubaydullo ugli (Ta’lim innovatsiyasi va integratsiyasi, 2023)
This article explores the establishment of a scientific-innovative infrastructure for cotton -textile clusters in Uzbekistan. The author has put forward suggestions to enhance the scientific-innovative infrastructure, which will facilitate integration among cluster participants, boost production efficiency, commercialize innovative projects, and create and execute programs for the progress of cotton textile clusters.